INVESTIGATION OF PRESERVICE TEACHERS’ CONCEPTUAL UNDERSTANDING IN STOICHIOMETRY USING MODIFIED CERTAINTY OF RESPONSE INDEX (CRI) - Chanifah, Siti; Mulyatun, Mulyatun; Lathifa, Ulya (Unnes Science Education Journal, 2019)
Conceptual understanding is very important for the preservice teachers to master it. Stoichiometry is one of the basic concepts in chemistry which applied to almost concepts. This study aims to determine the percentage of students who understand the concept, not understand the concept, and having misconceptions in stoichiometry. Furthermore, this research purposes to identify the type of misconceptions. To investigate students’ conceptual understanding, we use a modified CRI technique (diagnostic test with multiple choice and open reason with the scale of confidence level) and interview. The results show that the average percentage of students who understood the concept is 53.96%, having misconception is 16.20% and did not understand the concept is 29.83%. There are 19 types of misconceptions. The causes of misconceptions include deficiency impediment, ontological impediment, and fragmentation impediment.